Of Lime-Belite Materials Obtained on the Basis from Local Marls of the Republic of Karakalpakstan - Abylova A.Zh; Bekbosynova R.Zh; Nauryzbayeva Z.Sh; Daniyarova S.K; Saipov A.A; Kalilaev T.T. (Zien Journals, 2022)
The article presents the results of the chemical and physico - mechanical properties of silicate brick based on calcite – whiteite binders. The results of the mineralogical composition of marl and the temperature of the heat treatment of calcareous – calcite binders (LBB) are presented. General technology for producing silicate products.
Keywords: quartz sand; marl; lime; cement